Programa de qualificação de fornecedores de leite e indicadores da atividade leiteira: um estudo com produtores do estado do Rio Grande do Sul, Brasil - Garzão, Marlussi de Oliveira (2023)
Effective management of processes in milk production is crucial for achieving high quality, which is valued by dairy companies and consumers. The current regulations in Brazil, IN76 and IN77/2018, establish procedures to ensure the quality of milk produced in our country, with the Supplier Qualification Program for Milk (SQPM) being one of the highlighted measures. This research aimed to analyze the quality, composition, and price indicators of milk collected by an agricultural cooperative in Rio Grande do Sul. The cooperative provided a database (2012 to 2022 - 579 properties) where the evolution of these indicators was assessed. Comparative analyses were then conducted on the same indicators before and after the implementation of SQPM (2019 to 2022 - 426 properties). Significant improvements were observed in the parameters of milk quality and composition, indicating that SQPM can be an important tool in achieving the objectives of the current legislation and improving the quality of raw milk. The monthly average parameters of Somatic Cell Count (SCC) indicated that all the numbers found were below the maximum limit of the current legislation (300,000 CFU/mL - IN76). The monthly averages of SCC indicated that the highest averages occurred during the summer and autumn months. Milk protein content showed higher numbers during the autumn and winter seasons, while lower numbers were observed during spring and summer. The recorded fat content was higher than the minimum values (3%) established by IN76, and the average total solids content was 11.37%. The perception of the producers regarding the program revealed some difficulties in adoption and adaptation when considering all the evaluated indicators. Nevertheless, one of the groups stood out in terms of progress and ease in implementing and adapting to SQPM on their property, and they also reported significant improvements in production and milking management.